Minimum weight design of vertically vibrating 3-D machine foundation coupled to layered half-space 1 - Sienkiewicz, Zbigniew; Wilczyński, Bogdan (Computer Assisted Methods in Engineering and Science, 2023)
Dynamic optimization problem for a machine rigid block foundation on an inhomogeneous soil is considered. The soil deposit under the base of block corresponds to a layer with linearly varying properties overlying a uniform half-space. Furthermore, the block may be surrounded by a backfill. The optimal designs of a vertically excited rectangular block foundation are found by iterative application of a sequential linear programming for a number of rationally inhomogeneous supporting media as well as for a uniform half-space. It illustrates the problem of adequate modelling of the nature of the soil profile and provides an insight into the action of the soil-foundation-machine system from the point of view of the long-term satisfactory performance and safety.